Ranma 1/2. 25·26 - Takahashi, Rumiko, 1957-; Thorn, Rachel (Shonen Sunday., 2016)
Ranma's latest challenge is Furinkan High's newest teacher, Hinako Ninomiya. She can drain an opponent's energy and transform from her childlike stature to a tall, sultry siren. Will Ranma defeat Hinako, or will he be the one who's schooled? Then, Akane reunites with a boy from her childhood who's dying of a wound she inflicted on him when they were young. With his fatal wound on her conscience, will Akane choose to stay with Shinnosuke until the bitter end?